EDUKASI KESEHATAN REPRODUKSI REMAJA PUTRI TENTANG PERSONAL HYGIENE SAAT MENSTRUASI: Kesehatan Reproduksi, Remaja Putri, Personal Hygine, Menstruasi - Hanum, Diyana Faricha; Rochmah, Noviatul; Nabila, Mahcica Afshokun (Indonesian Journal of Community Dedication in Health (IJCDH), 2021)
Abstract Adolescent reproductive health is a healthy condition that concerns the reproductive systems, functions and processes of adolescents. The importance of maintaining reproductive health for adolescents because adolescence is the best time to build good habits of maintaining hygiene, which can be an asset in the long term. Community service activities have been carried out at SMK Dharma Wanita, Gresik. Community Service is divided into several stages, namely: appointment of reproductive health cadres from the school and counseling on reproductive health education for female adolescents about personal hygiene during menstruation through videos uploaded on the youtube channel https://youtu.be/FZuNTxH8GrQ. Followed by questions and answers using the WhatsApp (WA) media. This community service was attended by 10 students who had been appointed as reproductive health cadres. And our YouTube is followed by 103 viewers, 32 likes and 18 subscribers. At the end of this community service activity, the hope is that it can make female adolescents students become counseling friends about adolescent reproductive health with peers and can prevent problems that may arise due to inaccurate personal hygiene during menstruation, so that teaching and learning activities run well and there is an increase in achievement for students. And our hope as health workers is that young women can be responsible for their reproductive health which will have an impact on their future as healthy women and mothers. Keywords: Reproductive health, female adolescents, personal hygiene, Menstruation